THE ACCURACY OF SENTENCE LEVEL IN ENGLISHINDONESIAN SUBTITLE OF ‘THE END OF THE F***ING WORLD – SEASON 2 - Akmala Ashlikhatina; Januarius Mujiyanto (JELLT (Journal of English Language and Literature Teaching), 2021)
This study attempts to find the accuracy of sentence level ((1) simple sentence, (2) compound sentence, (3) complex sentence, (4) compound-complex sentence) in English-Indonesian subtitle of The End of the F***ing World – Season 2. The researcher collected the data by watching the series in English and Indonesian subtitle, then these subtitle were categorized into those 4 types of sentences. These data were checked its accuracy using a theory from Nababan et al. (2012). The researcher found 461 data of simple sentences and 445 (96.7%) of them are accurate. Second one, the researcher found 67 data of compound sentences and 63 (94%) of them are accurate. Third one, the researcher found 43 data of complex sentences and 41 (95%) of them are accurate. Last one, the researcher found 8 data of compound-complex sentences and 7 (87.5%) of them are accurate. Based on that, the researcher can say that the subtitle is accurate, but I still found some mistakes that are considered as major ones because these might cause ambiguity or misunderstanding to audiences, that’s why we – as the audiences – also need to be more careful in reading some subtitle.